Urgensi Bilingualisme dalam Kemampuan Literasi untuk Calon Guru Matematika: Sebuah Studi Literatur - Agnes Teresa Panjaitan (Journal on Education, 2024)
This research was conducted by analyzing various research articles on the urgency of bilingualism for prospective mathematics teachers. In this research, data collection is done by looking for articles that specifically discuss bilingualism in mathematics. There are 11 research articles from national and international journals. The results of the analysis of the article concluded that the ability of English mathematics (bilingualism) provides various benefits for prospective teachers. One of them is increased literacy skills due to various sources of learning using the English language. Another benefit is that motivation to welcome the future is rising. Students realize that English is an ability that can prepare 21st-century skills by preparing one of the communication skills in the learning process.